Capsule Production and Glucose Metabolism Dictate Fitness during Serratia marcescens Bacteremia - Mark T. Anderson (American Society for Microbiology, 2017)
ABSTRACT Serratia marcescens is an opportunistic pathogen that causes a range of human infections, including bacteremia, keratitis, wound infections, and urinary tract infections. Compared to other members of the Enterobacteriaceae family, the genetic factors that facilitate Serratia proliferation within the mammalian host are less well defined. An in vivo screen of transposon insertion mutants identified 212 S. marcescens fitness genes that contribute to bacterial survival in a murine model of bloodstream infection. Among those identified, 11 genes were located within an 18-gene cluster encoding predicted extracellular polysaccharide biosynthesis proteins. A mutation in the wzx gene contained within this locus conferred a loss of fitness in competition infections with the wild-type strain and a reduction in extracellular uronic acids correlating with capsule loss. A second gene, pgm, encoding a phosphoglucomutase exhibited similar capsule-deficient phenotypes, linking central glucose metabolism with capsule production and fitness of Serratia during mammalian infection. Further evidence of the importance of central metabolism was obtained with a pfkA glycolytic mutant that demonstrated reduced replication in human serum and during murine infection. An MgtB magnesium transporter homolog was also among the fitness factors identified, and an S. marcescens mgtB mutant exhibited decreased growth in defined medium containing low concentrations of magnesium and was outcompeted ~10-fold by wild-type bacteria in mice. Together, these newly identified genes provide a more complete understanding of the specific requirements for S. marcescens survival in the mammalian host and provide a framework for further investigation of the means by which S. marcescens causes opportunistic infections. IMPORTANCE Serratia marcescens is a remarkably prolific organism that replicates in diverse environments, including as an opportunistic pathogen in human bacteremia. The genetic requirements for S. marcescens survival in the mammalian bloodstream were defined in this work by transposon insertion sequencing. In total, 212 genes that contribute to bacterial fitness were identified. When sorted via biological function, two of the major fitness categories identified herein were genes encoding capsule polysaccharide biogenesis functions and genes involved in glucose utilization. Further investigation determined that certain glucose metabolism fitness genes are also important for the generation of extracellular polysaccharides. Together, these results identify critical biological processes that allow S. marcescens to colonize the mammalian bloodstream.